Quantitative and Qualitative Evaluation of Breast Cancer Prognosis: A Sonographic Elastography Study - You, Yue; Song, Yu; Li, Songxiu; Ma, Zhenhai; Bo, Huaying (Medical science monitor, 2019)
BACKGROUND Breast cancer is one of the most commonly diagnosed cancers in women worldwide, and sonographic elastography has previously demonstrated good performance in detecting breast malignancies. However, the exact relationship between elastographic measures and clinical prognostic factors is still not well understood. Thus, the aim of this study was to evaluate any associations between major clinical prognostic factors and strain elastography and to validate the diagnostic value of elastography in breast cancer. MATERIAL AND METHODS A total of 373 subjects with breast masses, of which 196 were benign and 177 were malignant, were included in the study. All subjects underwent routine ultrasound examination and strain elastography before biopsy. The elastographic measures - strain ratio (SR) for qualitative measures and Tsukuba score (TS) for quantitative measures - were obtained and compared with prognostic factors, including nuclear grade, lymph node status, estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor 2 (HER-2). The SR demonstrated the best diagnostic performance in differentiation between malignant and benign lesions. RESULTS With the best cut-off value at 2.42, the SR achieved a sensitivity of 96.0% and specificity of 98.5%. Moreover, higher SRs and TSs were associated with breast lesions with a high nuclear grade and lymph node metastasis and with being ER-negative, PR-negative, and HER-2 negative. CONCLUSIONS Elastography is a useful imaging technique in differentiating benign breast masses from malignant ones. The strong relationship between prognostic factors and elastographic measures also demonstrated its excellent performance in predicting the prognosis of breast malignancies.